2021
DOI: 10.12659/ajcr.931589
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal Abscess in a Patient with Neutropenia and Refractory Acute Myeloid Leukemia: To Operate or not to Operate?

Abstract: Patient: Male, 56-year-old Final Diagnosis: Perianal abscess Symptoms: Fever • gluteal pain • septic shock Medication: — Clinical Procedure: Debridement • fistulotomy • incision and drainage Specialty: Hematology • Infectious Diseases • Surgery Objective: Rare disease Background: Anorectal infections occur in 5% to 9% of patients with hematological malignancies, including acute myeloid leukemia, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, most existing studies have focused on the diagnosis and treatment after perianal infection has occurred7 8 and no risk prediction model has been established. Therefore, to help medical staff promptly screen patients at a high risk of perianal infection during chemotherapy, this study comprehensively identified risk factors for perianal infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, most existing studies have focused on the diagnosis and treatment after perianal infection has occurred7 8 and no risk prediction model has been established. Therefore, to help medical staff promptly screen patients at a high risk of perianal infection during chemotherapy, this study comprehensively identified risk factors for perianal infection.…”
Section: Introductionmentioning
confidence: 99%